EXAMINING CYBERSECURITY VULNERABILITIES IN CONSTRUCTION COMPANIES IN NIGERIA - Albert, Idowu; Osadola, Ayodeji Opeyemi (FUDMA Journal of Sciences, 2026)
The increasing adoption of digital technologies in the construction industry has improved project coordination, communication, and efficiency. Tools such as Building Information Modeling (BIM), cloud-based platforms, and mobile communication systems are now widely used by construction firms. However, the growing reliance on these digital systems has also exposed construction companies to significant cybersecurity risks. In Nigeria, where the construction sector plays a key role in infrastructure development, many firms lack adequate cybersecurity preparedness, making them vulnerable to cyber threats. This study examines the vulnerabilities of construction companies to cybersecurity threats within Lagos State construction industry. A quantitative research approach was adopted using a cross-sectional survey design. Data were collected from 300 construction professionals, including architects, builders, engineers, quantity surveyors, estate valuers, and town planners, through a structured questionnaire. The data were analyzed using descriptive statistics, a one-sample t-test, and exploratory factor analysis with the aid of SPSS. The findings revealed several major cybersecurity vulnerabilities, including the use of unsecured networks, risks associated with remote work, limited cybersecurity resources, unpatched software vulnerabilities, insufficient data protection, and inadequate access control. The t-test results confirmed that all identified vulnerabilities were statistically significant (p < 0.05). Factor analysis further grouped the vulnerabilities into three key components: technical weaknesses, organizational and policy gaps, and human and external risks. The study concludes that strengthening cybersecurity policies, improving awareness, and investing in secure digital systems are essential for protecting construction firms from cyber threats and ensuring safer digital operations in the Nigerian construction industry.
Keywords: Cybersecurity; Construction industry; Cyber threats; Digital technologies; Nigeria